Análise do modelo de progressão na Assembleia Legislativa do estado de Goiás – impactos motivacionais - Santos, Santiago Francisco Alves (2021)
The Brazilian public administration works with two concepts related to the career evolution of civil servants: progression and promotion. Public organizations adopt their own requirements for professional development, with, in general, remuneration increases for each standard or class achieved. Such incentives, however, should not be limited to financial aspects only when the intention is to influence the employees' motivation and consequently impact productivity. Focusing on the Legislative Assembly of the State of Goiás (ALEGO), this research addressed the career path to which permanent government employees are subject, as well as the models of professional evolution adopted by other Legislative Assemblies in the country for comparison purposes. The model conceived by ALEGO was also correlated with motivational theories. The general objective of the study was to investigate whether ALEGO’s professional development model influenced the motivation of employees and, if so, to assess whether positively or negatively. The study also found that the implementation of a new career path that considers individuality for motivational purposes does not violate constitutional principles. Descriptive research was developed, framed as a case study. Structured interviews with 12 permanent employees of ALEGO were carried out, which integrated precepts of various motivational theories. Currently, ALEGO only considers the temporal gap for professional advancement, not having or using metrics to measure the productivity of its employees. In the rest of the country, data obtained indicated the existence of legislative bodies that use a mixed system of progression/promotion, with a strong tendency towards the extinction of career paths that only consider length of service, opting in general for systems based on merit. The analysis of the career evolution system in face of motivational theories, through theoretical application according to the answers given by the interviewees, allowed the elucidation of gaps in the model adopted by ALEGO, which can prevent the servers from achieving maximum professional performance. Almost all employees interviewed (91.7%) were dissatisfied with the automatic progression and exclusively by length of service and, of these, all viewed positively systems considered more complete for professional development adopted in the rest of the country. As an intervention proposal, the remodeling of the current system of progression by length of service and the stipulation of goals to obtain an extra remuneration increase was idealized. The need for further technical studies to assess the project’s feasibility was verified not ruling out the indispensability of legislative approval.